Essentials of trauma anesthesia - Varon, Albert J.; Smith, Charles E., 1956- (Cambridge : Cambridge University Press, 2017)
Covering the most important topics in trauma anesthesia, this updated edition provides anesthesiology trainees and practitioners with a practical basis for managing trauma patients. Many recent advances in trauma care are identified, including paradigm shifts in the management of bleeding and coagulopathy, new neuromuscular blockade and anticoagulant reversal drugs, and updated clinical practice guidelines. This volume provides a concise, practical review of the essential elements in the care of the severely injured trauma patient, including emergency airway management, fluid and blood resuscitation, monitoring, coagulation therapy, regional and general anesthesia, and perioperative care. Edited by two of the most experienced trauma anesthesiologists in the United States, with chapters written by experts from leading US and Canadian trauma centers with the highest and most varied caseload of critically injured patients, Essentials of Trauma Anesthesia identifies new trends in surgery and anesthesiology practices that impact on the management of trauma patients.
Title from publisher's bibliographic system (viewed on 10 Nov 2017).
Keywords: Anesthesia in traumatology